Factors Influencing An Auditor's Ability To Detect Fraud: The Role Of Auditor Experience As A Moderating Variable (Empirical Study Of Public Accounting Firms In South Jakarta) - Yuwono, Bayu Tri; Sarwoko, Haris (Politeknik Negeri Ambon, 2025)
The ability of auditors to detect fraud is an intriguing topic to explore, considering that evidence in the field shows many companies still manipulate financial statements to present misleading depictions of their performance. This issue poses a significant challenge in supporting the vision of